Endovascular thoracic aortic repair in confirmed or suspected genetically triggered thoracic aortic dissection. - Asch, Federico M (2018)
CONCLUSIONS: TEVAR in patients with genetically triggered aortic dissections can be lifesaving in the acute setting though associated with high risk of retrograde aortic dissection in acute TBAD. For chronic dissection-related DTA aneurysmal degeneration, TEVAR could potentially be lifesaving in patients deemed too high risk for open surgical repair. Close postoperative surveillance is required, given the risk of subsequent device failure and need for reintervention. Because these circumstances are rare, multicenter prospective enrollment of patients with genetically triggered aortic disease is essential to delineate the indications for and risks of TEVAR in this heterogeneous population.
Copyright (c) 2018 Society for Vascular Surgery. Published by Elsevier Inc. All rights reserved.
METHODS: We analyzed data for patients with descending thoracic aorta (DTA) dissection treated with TEVAR from the National Registry of Genetically Triggered Thoracic Aortic Aneurysms and Cardiovascular Conditions (GenTAC). Enrolled patients had confirmed (syndromic or familial) or suspected genetically triggered thoracic aortic disease. The latter group includes patients with sporadic aortic dissection presenting at 50 years of age or younger in the absence of a family history or syndromic features.
OBJECTIVE: Endovascular repair in patients with connective tissues disorders is not recommended because of concern for repair failure. The aim of this study was to investigate thoracic endovascular aortic repair (TEVAR) outcomes in patients with confirmed or suspected syndromic and nonsyndromic genetically triggered thoracic aortic dissection.
RESULTS: Between 2006 and 2014, there were 371 patients with DTA dissection enrolled in GenTAC. TEVAR was performed in 31 cases (58.1% male; median age, 47 years; range, 21.3-65.6 years). Genetically triggered aortic dissection was confirmed in 18 cases, and an additional 13 cases had suspected genetically triggered dissection because of early onset of presentation. TEVAR was performed in nine patients with type A aortic dissection: five in conjunction with acute type A dissection repair and four in the chronic phase to treat aneurysmal degeneration of the residual dissected DTA (median interval to TEVAR, 2.1 years). TEVAR was also performed in 22 cases of type B aortic dissection (TBAD), 12 acute and 10 chronic (median interval to TEVAR, 1.6 years). There were no perioperative deaths. Median follow-up for all cases was 2 years (range, 0.4 month-7 years). Reinterventions after TEVAR were performed in 13 cases (41.9%). This included urgent repair of three retrograde ascending aorta dissections occurring after TEVAR for acute TBAD (25%) and seven thoracoabdominal repairs with stent graft explantation (22.6%) at a median of 7 months after TEVAR (range, 1-16.6 months).
Available online from MWHC library: 1995 - present, Available in print through MWHC library: 1999 - 2006
English
Keywords: *Aneurysm, Dissecting/su [Surgery]; *Aortic Aneurysm, Thoracic/su [Surgery]; *Blood Vessel Prosthesis Implantation; *Endovascular Procedures; Acute Disease; Adult; Aged; Aneurysm, Dissecting/dg [Diagnostic Imaging]; Aneurysm, Dissecting/ge [Genetics]; Aortic Aneurysm, Thoracic/dg [Diagnostic Imaging]; Aortic Aneurysm, Thoracic/ge [Genetics]; Aortography/mt [Methods]; Blood Vessel Prosthesis Implantation/ae [Adverse Effects]; Chronic Disease; Computed Tomography Angiography; Endovascular Procedures/ae [Adverse Effects]; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Postoperative Complications/et [Etiology]; Postoperative Complications/su [Surgery]; Registries; Reoperation; Retrospective Studies; Risk Factors; Time Factors; Treatment Outcome; United States; Young Adult; MedStar Heart & Vascular Institute; Journal Article